2009
DOI: 10.1095/biolreprod.108.075242
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Low-Density Detergent-Resistant Membrane Proteins in Intact and Acrosome-Reacted Mouse Sperm1

Abstract: Mammalian sperm become fertile after completing capacitation, a process associated with cholesterol loss and changes in the biophysical properties of the sperm membranes that prepares the sperm to undergo the acrosome reaction. Different laboratories have hypothesized that cholesterol efflux can influence the extent and/or movement of lipid raft microdomains. In a previous study, our laboratory investigated the identity of sperm proteins putatively associated with rafts. After extraction with Triton X-100 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 58 publications
4
45
0
2
Order By: Relevance
“…We can assume that the lack of CAV1 is not critical for sperm fertility, and it does not seem to be upregulated by other caveolin isoforms, although CAV2 is present in mouse sperm (Miranda et al 2009) but is unstable in the absence of CAV1 (Razani et al 2001). CAV3 is exclusively expressed in striated muscle cells and cardiac and skeletal muscles (Song et al 1996).…”
Section: Discussionmentioning
confidence: 92%
“…We can assume that the lack of CAV1 is not critical for sperm fertility, and it does not seem to be upregulated by other caveolin isoforms, although CAV2 is present in mouse sperm (Miranda et al 2009) but is unstable in the absence of CAV1 (Razani et al 2001). CAV3 is exclusively expressed in striated muscle cells and cardiac and skeletal muscles (Song et al 1996).…”
Section: Discussionmentioning
confidence: 92%
“…Deficient actin polymerization in Tssk6-null sperm Changes in the immunofluorescence pattern of sperm surface proteins during capacitation and acrosome reaction have been described previously (Miranda et al, 2009;Saxena et al, 1986;Primakoff and Myles, 2007;Selvaraj et al, 2007). It has been shown that changes in protein localization are at least in part due to actincytoskeleton dynamics (Saxena et al, 1986;Hernandez-Gonzalez et al, 2000).…”
Section: Tssk6 Localizes To the Sperm Headmentioning
confidence: 89%
“…Recently it was reported that Izumo relocalizes from the anterior acrosome where it is found in intact mouse spermatozoa, to other regions in the head engaged in fusion with the egg plasma membrane. Tssk6, a member of the testis-specific serine kinase family, is necessary for the movement of Izumo, and its role is mediated by the actin cytoskeleton (362,476).…”
Section: A Generalitiesmentioning
confidence: 99%